2020
DOI: 10.1364/oe.396928
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared resonant cavity light emitting diodes operating at 4.5 µm

Abstract: We report on a mid-infrared resonant cavity light emitting diode (RCLED) operating at the wavelength of 4.5 μm with narrow spectral linewidth at room temperature. Compared to a reference LED without a resonant cavity our RCLED exhibits (85x) higher peak intensity, (13x) higher integrated output power, (16x) narrower spectral linewidth and (7x) superior temperature stability. The device consists of a one-wavelength thick micro-cavity containing an Al 0.12 In 0.88 As/InAs 0.85 Sb 0.15 quantum well active region … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…In addition, they thinned and roughened the emission side of the structure to improve light outcoupling, resulting in randomization of light direction and reduction of internal reflection and light outcoupling. With their 400 × 400 µm cascaded superlattice Reprinted and edited with the permission from [87].…”
Section: Mir Light Emitting Diodes (Mir-leds)mentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, they thinned and roughened the emission side of the structure to improve light outcoupling, resulting in randomization of light direction and reduction of internal reflection and light outcoupling. With their 400 × 400 µm cascaded superlattice Reprinted and edited with the permission from [87].…”
Section: Mir Light Emitting Diodes (Mir-leds)mentioning
confidence: 99%
“…Most recently, efforts have been focused on mitigating the low output power with broadband emission spectra at room temperature for developing next-generation MIR-LEDs, and new approaches of structure modification to increase the power output have been devised. Al-Saymari's team presented two so-called resonant cavity LED (RCLED) systems [ 86 , 87 ]. In these systems grown on GaSb substrate, the optical extraction efficiency limited by the large refractive index mismatch between the semiconductor and air has been addressed by placing the active structure between two DBRs.…”
Section: Advancements In Mir Light Sources Beyond Lasersmentioning
confidence: 99%
See 2 more Smart Citations
“…It has previously been reported that the resonance peak wavelength shifts with temperature, with the majority of the shift attributed to changes in refractive indices of the cavity layers. [ 14,15 ] Figure 2b shows the temperature dependence of the resonant wavelength for the two devices. The gradient of the two fit lines shows clearly that the peak shift due to temperature is very similar for both devices— 0.27 nm/K for the InAsSb‐based device and 0.28 nm/K for the InAs‐based device.…”
Section: Optical Characterizationmentioning
confidence: 99%